2018
DOI: 10.1007/s00438-018-1483-9
|View full text |Cite
|
Sign up to set email alerts
|

First report on B chromosome content in a reptilian species: the case of Anolis carolinensis

Abstract: Supernumerary elements of the genome are often called B chromosomes. They usually consist of various autosomal sequences and, because of low selective pressure, are mostly pseudogenized and contain many repeats. There are numerous reports on B chromosomes in mammals, fish, invertebrates, plants, and fungi, but only a few of them have been studied using sequencing techniques. However, reptilian supernumerary chromosomes have been detected only cytogenetically and never sequenced or analyzed at the molecular lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…At least a half of these genes are transcriptionally active [ 71 ]. It should be noted that these genes are involved in cell division processes as well as the genes of B s of vertebrates [ 19 , 20 , 21 , 72 , 73 , 74 ]. However, the exact location and flanking regions of these genes are mostly unknown.…”
Section: Discussionmentioning
confidence: 99%
“…At least a half of these genes are transcriptionally active [ 71 ]. It should be noted that these genes are involved in cell division processes as well as the genes of B s of vertebrates [ 19 , 20 , 21 , 72 , 73 , 74 ]. However, the exact location and flanking regions of these genes are mostly unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to repetitive DNA, pseudogene-like sequences have also been reported to be located on Bs [56,74,75]. We assume that these pseudogenes might have formed as a result of intensive rearrangements and frequent sequence duplications in A chromosomes.…”
Section: Genome Composition Origin and Evolution Of Bsmentioning
confidence: 98%
“…Apart from the presence of transposons and pseudogenes/fragments of genes on Bs, the latest research studies [25,44,56,75,77,78,79] have also found protein coding intact genes that we call “B essential genes” (see definitions in Box 1) which might be critical for the survival and transmission of Bs during their earlier stages of evolution (see details in next topic section). To create a reference of B-linked genes, we have organized a database that contain a list of genes detected in different species (Supplementary Dataset S1).…”
Section: Genome Composition Origin and Evolution Of Bsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we should note that the revealed B chromosomes open a new possibility for analysis of amplified DNA repeats in M. mirumnovem. Microdissected DNA libraries can be generated from B chromosomes and then used for NGS sequencing, as was done previously for the Bs in some species of different taxa [45][46][47]. The study of B chromosomes in M. mirumnovem, including the generation of microdissected libraries and their sequencing is in progress.…”
Section: Differentiation Of Large Chromosomes and Origin Of B Chromosmentioning
confidence: 99%